Practical approaches to examination of women with abnormal vaginal discharge: a review of evidence-based recommendations 2021 - O.A. Burka; A.V. Shumytskyi; L.M. Semeniuk; O.D. Koltok; V.Y. Dobosh; H.O. Islamova (Publishing House TRILIST, 2021)
Abnormal vaginal discharge (AVD) is a syndrome that combines conditions of different origin (microbial/non-microbial) and of different anatomical localization (limited to vagina and exocervix/spreading from the endocervix to the pelvic organs) that cause discomfort and changes in the characteristics of vaginal discharge. Review objective: to systematize modern approaches to the diagnosis of the most common causes of AVD - bacterial vaginosis (BV), trichomoniasis, aerobic vaginitis (AV), vulvovaginal candidiasis (VVC) - in a practical context. Laboratory component of diagnosing the AVD causes should be complex due to the not fully understood mechanisms of regulation of vaginal biocenosis and changes in the virulence of opportunistic and pathogenic flora, leading to an increase in the frequency of mixed forms of vaginosis and their atypical course. The tasks of laboratory tests in AVD are determination of the sexually transmitted infections (gonorrhea, chlamydia, Mycoplasma genitalium) more often as a concomitant asymptomatic infection in combination with BV or another cause of AVD; confirmation of the suspected cause of AVD (BV, trichomoniasis, AV, VVC); differential diagnosis with more rare microbial causes (cytolytic vaginosis) and non-microbial causes. Vaginal pH and microscopy of vaginal discharge with an assessment according to the diagnostic criteria for dysbiosis are first line of available diagnostic tests of BV, AV and VVC. They make it possible to differentiate typical AVD causes from non-microbial AVD causes and rare causes of microbial AVD. Additionally, complex modern molecular methods for assessing the vaginal biocenosis can be used. Cultural methods play an important role in the diagnosis and treatment of recurrent/complicated VVC and AV. PCR for chlamydia, gonorrhea, trichomoniasis and Mycoplasma genitalium is a mandatory component of a comprehensive test in patients with suspected BV, AV or mixed dysbiosis. Patients diagnosed with BV or trichomoniasis has to be tested for HIV and sexually transmitted infections.